Influence of System Parameters on Compressibility of Chopped Water Hyacinth (Eichhornia crassipes) - Mathur, S M; Singh, Pratap; Mehta, A K (Journal of Agricultural Engineering, 2003)
Chopped samples of fresh water hyacinth were compressed in a closed cylindrical die at 10 levels of pressures, five levels of die charges and five levels of compression speeds on Houn’s Field Universal Testing Machine. The complete compression process was observed and relationships were developed among compression ratio and compression pressures, die charges and compression speeds. The relationship between compression ratio and compression pressure followed the simple power law while a linear trend was found with die-charge. The result shows that with the increase in die-charge the increase in compression ratio decreases for all compression pressures. Compression ratio was found to increase with the increase in compression pressure for all die charge. There was a significant difference in reduction in compression ratio while moving from one pressure level to another and from one die charge to another die charge. Maximum compression ratio found was 17.52 for die-charge of 0.020 kg and minimum was 4.95 for die charge of 0.040 kg, at a maximum compression pressure of 2.54 MPa.